Body mass and growth rates in captive chimpanzees (Pan troglodytes) cared for in African wildlife sanctuaries, zoological institutions, and research facilities. Issue 1 (11th July 2022) - Curry, Bryony A.; Drane, Aimee L.; Atencia, Rebeca; Feltrer, Yedra; Howatson, Glyn; Calvi, Thalita; Palmer, Christopher; Moittie, Sophie; Unwin, Steve; Tremblay, Joshua C.; Sleeper, Meg M.; Lammey, Michael L.; et al.
Abstract: Captive chimpanzees ( Pan troglodytes ) mature earlier in body mass and have a greater growth rate compared to wild individuals. However, relatively little is known about how growth parameters compare between chimpanzees living in different captive environments. To investigate, body mass was measured in 298 African sanctuary chimpanzees and was acquired from 1030 zoological and 442 research chimpanzees, using data repositories. An analysis of covariance, adjusting for age, was performed to assess same‐sex body mass differences between adult sanctuary, zoological, and research populations. Piecewise linear regression was performed to estimate sex‐specific growth rates and the age at maturation, which were compared between sexes and across populations using extra‐sum‐of‐squares F tests. Adult body mass was greater in the zoological and resarch populations compared to the sanctuary chimpanzees, in both sexes. Male and female sanctuary chimpanzees were estimated to have a slower rate of growth compared with their zoological and research counterparts. Additionally, male sanctuary chimpanzees were estimated to have an older age at maturation for body mass compared with zoological and research males, whereas the age at maturation was similar across female populations. For both the zoological and research populations, the estimated growth rate was greater in males compared to females. Together, these data contribute to current understanding of growth and maturation in this species and suggest marked differences between the growth patterns of chimpanzees living in different captive environments. Abstract : Piecewise linear regression estimated that male chimpanzees ( Pan troglodytes ) housed in African sanctuaries had a slower rate of growth and an older age at maturation for body mass compared with their zoological and research counterparts. In contrast, male zoological and research populations had a similar growth rate and age at maturation. Highlights: African sanctuary chimpanzees are lighter compared with their zoological and research counterparts. Additionally, sanctuary chimpanzees have a slower growth rate compared to zoological and research populations, and male sanctuary chimpanzees have an older age at maturation. Male sanctuary chimpanzees have a slower growth rate and an older age at maturation compared to zoological and research males.